Speeches and declarations: a war of words - Reyes Rodríguez, Antonio (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2006)
The use of language is always manipulated to convey a goal of the speaker in order to have an effect on the hearer. Symbolic power is always present in speech. Politicians understand and harness the power of words to explain or justify acts in order to encourage, perhaps even force, people to support them, even if this support implies a risk to their lives. Following Bourdieu's (2001), Elster's (1986, 1994) and van Dijk's (1993, 1997a, 1997b, 2005) ideas, in particular, amongst others', this paper analyzes the speeches and declarations of George W. Bush, President of the United States, from September 11,2001 leading up to the 2003 attack on Iraq, in an attempt to decode the underlying intentions of the messages and strategies which he has used to justify military action, in what he and his administration call 'the war on terrorism'. This paper focuses on the linguistic representations of war and their implications (van Dijk, 2005), on the way in which war is linguistically and rhetorically constructed, particularly in the period of build-up to action. This study will propose a theoretical model of the chronological discursive phases of development of a rhetoric of war, culminating in military action with general public support domestically. Finally, I would like to introduce the term 'ideologically suggestive co- placement' as a linguistic power tactic to link factually unrelated objects (persons, nations, events, concepts) by presenting them within a simple clause or sentence, to intentionally create a link between these objects, between their connotations in the listener's mind, simply by their simultaneous mention. This term is presented as a new tool for future discourse analysis studies.